Marine Culture of Northeast Vietnam: Approaching from the Theory of Culture Ecology - Nam Thanh Nguyen (International Society of Philosophy and Cosmology, 2020)
The purpose of this paper is to contribute to further clarifying the characteristics of marine culture in the Northeast of Vietnam from the theory of cultural ecology. The research results of the article will also be a scientific basis to contribute to the study of Vietnam's sea and islands from the science of culture. In order to carry out this research, the author uses an analytical-synthesis method, which is used to deeply understand the research object, combining a comparative approach to show the similarities and differences between the marine culture of Northeast Sea and some other areas in Vietnam. The author attaches special importance to the practical survey method: participating in cultural activities of residents of some localities in the Northeast Sea of Vietnam (such as Quan Lan Island, Co To Island, Cat Ba Island...), and conducting interviews with people for the purpose of truly describing phenomena related to marine culture. Previous studies in Vietnam only focused on describing the appearance. They stated the values of Vietnamese coastal culture and some localities in the Northeast, but the theory of approach in marine culture research is unclear. This research uses the theoretical framework of cultural ecology to affirm: the people in the Northeastern region of Vietnam with their thinking have created ways to adapt to the natural environment and always creating material and spiritual values that bring about the highest adaptation to nature to benefit their life activities. The research results of this article can be used as a reference for the culture of the islands in the Northeast in particular and the Vietnamese culture in general, including theoretical research on marine culture, as well as the analysis of marine cultural characteristics from cultural ecology theory